Cobalt-titanium multilayer thin films: Effect of thickness of titanium spacer layer on impedance properties - Senturk, E.; Erkovan, M.; Okutan, M.; Kosemen, A.; Ozturk, S.; Sahin, Y. (Elsevier Sci Ltd, 2015)
We investigated the impedance parameters of cobalt titanium (Co-Ti) multilayer thin films deposited on native oxidized Si (100) substrate under ultra-high vacuum (4 x 10(-8) mbar) by magnetron sputtering at room temperature. Electrical properties of Co/Ti/Co multilayer films were analyzed depending on the thickness of Ti spacer layer with the impedance spectroscopy as a function of frequency. Co/Ti multilayer films exhibited dielectric relaxation in both real and imaginary part of dielectric constants at the kilohertz frequency region and piezoelectric properties at the megahertz frequency region. We determined that the fabricated multilayer films have complex and super imposed type behavior when DC conductivity is used at lower frequency, resonance event and relaxation properties. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Multilayer thin films; Piezoelectric; Impedance spectroscopy; Dielectric properties